Reception Theory Concept and Origin - An Applied Model Poem (After a Year) by the poet Dr. Ghazi Al-Qusaibi - Alawadi, Hamda Ebrahim (Journal of Arabic Language Sciences and Literature, 2022)
The research discusses the Theory of Reception in Arabic literature. It also presents the theory historical roots, main principles and views that influenced Western and Arab literature. In addition, this paper discusses the most important pioneers who contributed to popularize Theory of Reception ideas. The paper will also discuss emergence from different schools of literature, these schools have emerged from reception principles between the writer and his literary work. The research highlights formulated concepts to clarify the ideas of the theory, and present different points of view to defend its ideas. We will also highlight the reader’s role in analyzing the text, the reflection of his thoughts and psychological needs. This is due to this theory’s influence on readers which is considered a cornerstone of literary criticism.